Revising public agricultural support to mitigate climate change - Searchinger, Timothy D.; Malins, Chris; Dumas, Patrice; Baldock, David; Glauber, Joseph W.; Jayne, Thomas S.; Huang, Jikun; Marenya, Paswell (World Bank, 2020)
Agriculture generates roughly one-quarter of global greenhouse gas emissions. By 2050, without major mitigation efforts, agricultural emissions are likely to reach levels that would make meeting global climate targets practically unachievable. Meanwhile, countries that produce two-thirds of the world's agricultural output provided US$600 billion per year in agricultural financial support on average from 2014 to 2016. By evaluating these support programs, both overall and with six case studies, this report finds that many governments have moved to make their farm support less likely to distort what farmers produce, but only a modest portion of programs support environmental objectives, and even fewer support the mitigation of climate change. Out of US$300 billion in direct spending, only 9 percent explicitly supports conservation, while another 12 percent supports research and technical assistance. Instances in which receiving government funding is contingent upon supporting environmental objectives provide models on which to build but so far have produced only modest environmental benefits. Because crop and pasture yields need to grow dramatically to avoid more deforestation and other conversion of native habitats, mitigation priorities include help for farmers to boost yields and livestock productivity. Yet to avoid inadvertently encouraging more conversion, this aid must be conditioned on the protection of forests and other native areas. Overall, climate-oriented support for agriculture should have as a guiding principle increasing the efficient use of land and other natural resources. Incentive programs should be structured so that they offer graduated payments for higher climate performance. Governments should also prioritize coordinated projects across multiple producers to explore critically needed innovations in farm management, and should support those projects with research and technical assistance.